Demand Price Elasticity and Taxes on the Consumption of Sugar Sweetened Beverages in Argentina - Maceira, Daniel (2018)
Background: Currently there is an important debate in Argentina about the health and economic burden associated with chronic non-communicable diseases, and the potential impact associated with the high consumption of sugar-sweetened beverages (SSB) in children and adults. The objective of this study is to assess the consumption of SSB in Argentina, to estimate the own price, cross-price and income elasticity of the demand for each type of beverage, and to simulate the effect of a price increase via taxes on the quantities consumed. Methods: Household micro-data was used to determine expenditure, purchased quantities, and implicit prices of different types of beverages (sodas, flavored waters, juices, etc.). This information was taken from the National Household Expenditure Survey (ENGHo) 2004/2005 and 2012/2013. Own price, cross price and income elasticity were estimated using the Almost Ideal Demand System (AIDS). Results: The own price elasticity of SSB presented values ranged between -1.10 and -1.15 (depending on the household income quintile). Therefore, if price increases of 10% via taxes, the quantity consumed of these beverages would be reduced between 11.0 and 11.5%. The income elasticity of the demand for SSB was estimated between 0.95 and 0.99, which implies that with an increase of 10% of household income, the quantity demanded increases between 9.5 and 9.9% (depending on the household income quintile). Conclusions: The consumption of SSB is sensitive to the increase in prices in Argentina. From a public health perspective, this suggests that a tax policy for these beverages would have a positive and effective effect in reducing their consumption.